2022
DOI: 10.3390/healthcare10040742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Multiple Chronic Conditions on Medical Costs among Older Adults in South Korea

Abstract: This study aims to analyze the relationship between cognitive function and out-of-pocket cost of the state change of multiple chronic conditions in individuals aged 60 or older. Data from the 2014 to 2018 Korean Longitudinal Study of Aging were used for 2202 older adults who were cognitively “normal” at the start of the survey. Four status change groups were established (“Good→ Good,” “Good→ Bad,” “Bad→ Good,” and “Bad→ Bad”) according to the change in the number of chronic diseases. Generalized estimating equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…23 This might be due to multiple medical conditions elderly people face such as chronic disease and different musculoskeletal diseases. 25,26 The results of the study also showed that male patients had a significantly higher requirement for palliative care compared to female patients, which was five times that of their counterpart (AOR=5.31, 95% CI=1.68-11.79). This result is quite different from the study done at Tikur Anbessa (Black Lion) Hospital with the finding that none of socio-demographic characteristics were determinant factors of pain.…”
Section: Discussionmentioning
confidence: 83%
“…23 This might be due to multiple medical conditions elderly people face such as chronic disease and different musculoskeletal diseases. 25,26 The results of the study also showed that male patients had a significantly higher requirement for palliative care compared to female patients, which was five times that of their counterpart (AOR=5.31, 95% CI=1.68-11.79). This result is quite different from the study done at Tikur Anbessa (Black Lion) Hospital with the finding that none of socio-demographic characteristics were determinant factors of pain.…”
Section: Discussionmentioning
confidence: 83%
“…Referring to existing studies, 11 , 33 , 34 we controlled for a number of variables that influence the utilization and cost of health care services for the older adults, including age, gender (male = 0, female = 1), residence (rural = 0, urban = 1), education level (primary and below = 0, middle and above = 1), marital status (other = 0, cohabited = 1), health insurance coverage (no = 0, yes = 1), comorbidity (no = 0, yes = 1), smoking status (none = 1, quit = 2, still = 3), drinking status (none = 1, quit = 2, still = 3), body mass index (BMI) (underweight = 1, normal weight = 2, overweight = 3, obesity = 4), activities of daily living (ADL) score, annual household income per capita.…”
Section: Methodsmentioning
confidence: 99%
“…Referring to existing studies [12,19,20], we controlled for a number of variables that in uence the utilization and cost of healthcare services for the elderly in the model, including age, gender (male = 0, female = 1), residence (rural = 0, urban = 1), education level (primary and below = 0, middle and above = 1), marital status (other = 0, cohabited = 1), health insurance coverage (no = 0, yes = 1), smoking status (none = 1, quit = 2, still = 3), drinking status (none = 1, quit = 2, still = 3), body mass index (BMI) (underweight = 1, normal weight = 2, overweight = 3, obesity = 4), activities of daily living (ADL), annual household income per capita.…”
Section: Covariatesmentioning
confidence: 99%